Lunar analog study using portable gamma-ray neutron detector: Radiochemical mapping of silicic-to-basaltic volcanic terrains in the San Francisco Volcanic Field, Arizona - Deniz Ölçek; Craig Hardgrove; Thomas Prettyman; Amber L. Gullikson; Kristen A. Bennett; Kerri L. Donaldson Hanna; Lena Heffern; Margaret Landis (Icarus, 2026)

Advancing conservation through virtual livestock fencing - Drew E. Bennett; Travis Brammer; Jerod A. Merkle; Kurt T. Smith; Shawn Regan; Temple Stoellinger; Arthur Middleton; Kristin Barker; Jacob P. Hochard; Patrick E. Lendrum; Erin Welty; Craig Benjamin; et al. (Biological Conservation, 2026)

Overriding influence of climate on future carbon stocks in Australian temperate forests - Bianca J. Pickering; Denis Kultaev; Craig R. Nitschke; Erica Marshall; Dan Ababei; Trent D. Penman; Lauren T. Bennett (Science of The Total Environment, 2026)

The 4E-BPs as Translational Regulators in Neurological Disorders: Molecular Mechanisms and Therapeutic Potential - Sindhu S. Baskarapantula; Venkata Surya Kumar; Priyajit Changdar; Debashree Chakraborty; Yogendra Nayak; Albert R. La Spada; Craig L. Bennett; Somasish G. Dastidar (Molecular Neurobiology, 2026)
Protein translation is essential for maintaining the optimal functioning of the human nervous system. The 4E-Binding proteins (4E-BPs) are central regulators of this process, acting on the initiation factor eIF4E. Three homologs 4E-BP1, 4E-BP2, and 4E-BP3, are differentially expressed, with the phosphorylation state controlling cap-dependent translation in response to diverse physiological inputs, including growth factors, cytokines, hormones, nutrient availability, and signaling cascades converging on kinases such as mTOR. Dysregulation of 4E-BP activity has been implicated in multiple disease contexts, including neurodegenerative disorders (e.g., Parkinson’s disease, Alzheimer’s disease), neurodevelopmental disorders (e.g., Autism spectrum disorder, Epilepsy), neuropsychiatric conditions (e.g., Depression, Schizophrenia), and autoimmune diseases (e.g., Multiple sclerosis, Guillain–Barré syndrome). We aim to explore the importance of 4E-BPs through a neurological perspective and understand their role as therapeutic targets. In this review, we provide a comprehensive analysis of the three 4E-BP homologs in the central nervous system, emphasizing the CNS-specific dominance of 4E-BP2 and its link to synaptic plasticity and cognitive function. We further examine and provide mechanistic insights into how 4E-BPs contribute to disease pathogenesis, highlighting both shared and disorder-specific features. Finally, we discuss current therapeutic strategies aimed at modulating the mTOR/4E-BP axis, outline the limitations of existing approaches and identify emerging avenues for drug development. Together, these perspectives underscore the potential of 4E-BPs as both therapeutic targets and biomarkers in neurological disease.

Addressing key issues and knowledge gaps in resilience science for agriculture - Shana M. Sundstrom; Tala Awada; Elena M. Bennett; Brandon Bestelmeyer; Jennifer Hodbod; Anna Pacheco; Sheri Spiegal; Craig R. Allen (Agricultural Systems, 2025)

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Marine reserve use by a migratory coastal shark, Carcharias taurus - Ross G. Dwyer; Michaela Rathbone; Deborah L. Foote; Mike Bennett; Paul A. Butcher; Nicholas M. Otway; Brett M. Louden; Fabrice R.A. Jaine; Craig E. Franklin; Carley Kilpatrick (Biological Conservation, 2023)

A global biological conservation horizon scan of issues for 2023 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Holly M. Butterworth; Mick N. Clout; Isabelle M. Côté; Jason Dinsdale; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice Hughes; et al. (Trends in Ecology & Evolution, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Structural diversity underpins carbon storage in Australian temperate forests - Cristina Aponte; Sabine Kasel; Craig R. Nitschke; Mihai A. Tanase; Helen Vickers; Linda Parker; Melissa Fedrigo; Michele Kohout; Paloma Ruiz‐Benito; Miguel A. Zavala; Lauren T. Bennett (Global Ecology and Biogeography, 2020)
Aim Forest carbon storage is the result of a multitude of interactions among biotic and abiotic factors. Our aim was to use an integrative approach to elucidate mechanistic relationships of carbon storage with biotic and abiotic factors in the natural forests of temperate Australia, a region that has been overlooked in global analyses of carbon‐biodiversity relations. Location South‐eastern Australia. Time period 2010–2015. Major taxa studied Forest trees in 732 plots. Methods We used the most comprehensive forest inventory database available for south‐eastern Australia and structural equation models to assess carbon‐storage relationships with biotic factors (species or functional diversity, community‐weighted mean (CWM) trait values, structural diversity) and abiotic factors (climate, soil, fire history). To assess the consistency of relationships at different environmental scales, our analyses involved three levels of data aggregation: six forest types, two forest groups (representing different growth environments), and all forests combined. Results Structural diversity was consistently the strongest independent predictor of carbon storage at all levels of data aggregation, whereas relationships with species‐ and functional‐diversity indices were comparatively weak. CWMs of maximum height and wood density were also significant independent predictors of carbon storage in most cases. In comparison, climate, soil, and fire history had only minor and mainly indirect effects via biotic factors on carbon storage. Main conclusions Our results indicate that carbon storage in our temperate forests was underpinned by tree structural diversity (representing efficient utilisation of space) and by CWM trait values (representing selection effects) more so than by tree species richness or functional diversity. Abiotic effects were comparatively weak and mostly indirect via biotic factors irrespective of the environmental range. Our study highlights the importance of managing forests for functionally important species and to maintain and enhance their structural complexity in order to support carbon storage.

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Quantifying the effect of soil moisture content on segmenting root system architecture in X-ray computed tomography images - Susan Zappala; Stefan Mairhofer; Saoirse Tracy; Craig J. Sturrock; Malcolm Bennett; Tony Pridmore; Sacha J. Mooney (Plant and Soil, 2013)

Does productivity drive diversity or vice versa? A test of the multivariate productivity–diversity hypothesis in streams - Bradley J. Cardinale; Danuta M. Bennett; Craig E. Nelson; Kevin Gross (Ecology, 2009)
The idea that productivity regulates species diversity is deeply ingrained in the field of ecology. Yet, over the past few decades, an increasing number of experiments have shown that species diversity controls, rather than simply responds to, biomass production. These contrasting perspectives have led to a seeming paradox: Is diversity the cause or the consequence of biological production? Here we present empirical evidence for the multivariate productivity–diversity (MPD) hypothesis, which argues that differing perspectives on productivity–diversity relationships can be resolved by recognizing that historical research has focused on how resource supply regulates both the productivity and richness of local competitors, whereas more recent studies have focused on how the richness of a colonist pool regulates the efficiency by which resources are captured and converted into new tissue. The MPD hypothesis predicts that three pathways operate concurrently to generate productivity–diversity relationships in nature: (1) resource supply directly limits the standing biomass and/or rate of new production by primary producers, (2) producer biomass is directly influenced by the richness of species that locally compete for resources, and (3) resource supply rate indirectly affects producer biomass by influencing the fraction of species from a colonist pool that locally coexist. To examine whether this set of pathways explains covariation between productivity and diversity in natural streams, we used nutrient‐diffusing agar “patches” to manipulate resource supply rates in 20 streams throughout the Sierra Nevada mountain range, California, USA. We then measured the fraction of periphyton species from the stream colonist pool co‐occurring on each nutrient patch, as well as the standing biomass and rates of primary production. Natural patterns of covariation agreed with predictions of the MPD hypothesis. Algal biomass was an increasing function of nutrient supply, and an increasing function of local richness. The fraction of species from the colonist pool found co‐occurring on a patch was a concave‐down function of nutrient supply, causing nutrients to indirectly affect biomass via control over local richness. These results suggest that the MPD hypothesis is a viable explanation of patterns of diversity and productivity in natural stream ecosystems, and that it has potential to merge the historical view that productivity drives diversity with a parallel view that diversity drives productivity.

The World Can't Have Wild Tigers and Eat Them, Too - BRIAN GRATWICKE; ELIZABETH L. BENNETT; STEVEN BROAD; SARAH CHRISTIE; ADAM DUTTON; GRACE GABRIEL; CRAIG KIRKPATRICK; KRISTIN NOWELL (Conservation Biology, 2008)

A rare polyadenylation signal mutation of the FOXP3 gene (AAUAAA→AAUGAA) leads to the IPEX syndrome - Craig Bennett; Mary Brunkow; Fred Ramsdell; Kathy O'Briant; Qili Zhu; Ramsay Fuleihan; Ann Shigeoka; Hans Ochs; Phillip Chance (Immunogenetics, 2001)